Subjective perception of oral sensations in patients receiving chemotherapy with 5-fluorouracil and lecovorin for colon adenocarcinoma - Szmidt, Monika; Benedyk-Szeffer, Maja; Łagocka, Ryta; Górski, Maciej; Buczkowska-Radlińska, Jadwiga (Journal of Stomatology, 2015)
Aim of the study. To assess subjective oral perception in patients undergoing colon cancer chemotherapy with 5-FU and leucovorin. Materials and methods. The study was conducted on 66 patients (41 males and 21 females) undergoing adjuvant chemotherapy for colon cancer. All the examined participants received 5-fluorouracil and FA (folinic acid, leucovorin) chemotherapy in cycles of five consecutive days with a twenty-eight day intermission between them. Dental examination included anamnesis` and clinical examination. The interview` concerned subjective oral complains such as: bleeding gums, stomatalgia, mouth dryness, halitosis, dysgeusia (taste changes in the mouth), stomatopyrosis. Statistical analysis was performed using STATA 11. Normality of distribution of the data was tested using the Kolmogorov-Smirnov test. Independent t-test and U Mann-Whitney test were used to demonstrate differences between two groups. Results. 82% of the interviewed patients had oral subjective complains. These oral sensations included: burning sensation in the mouth, dysgeusia, bleeding gums, mouth dryness, mouth pain and fetor ex ore. The most frequent complaint was taste disorder (dysgeusia) 61%, the second problem was mouth dryness present in 41% of patients. Only 14% of subjects complained of either burning sensation or pain in the mouth. Females reported the sensation significantly more often. Patients receiving 1-4 cycles of chemotherapy reported halitosis more often than patients receiving 5 or more chemotherapy cycles. The number of chemotherapy cycles was found not to be important in the prevalence of other oral complaints. Conclusions. The study revealed that oral problems experienced by patients undergoing 5-FU and leucovorin therapy are many and diverse. The substantial number of patients during colon cancer therapy reported subjective oral sensations. The most frequent complaint concerned taste disorders and xerostomia.